The presence of a perseverative iterative style in poor vs. good sleepers - Barclay, N.L.; Gregory, A.M. (Journal of behavior therapy and experimental psychiatry, 2010)
Catastrophizing is present in worriers and poor sleepers. This study investigates whether poor sleepers possess a ‘perseverative iterative style’ which predisposes them to catastrophize any topic, regardless of content or affective valence, a style previously found to occur more commonly in worriers as compared to others. Poor (n=23) and good sleepers (n=37) were distinguished using the Pittsburgh Sleep Quality Index (PSQI), from a sample of adults in the general population. Participants were required to catastrophize 2 topics: worries about sleep, and a current personal worry; and to iterate the positive aspects of a hypothetical topic. Poor sleepers catastrophized/iterated more steps to a greater extent than good sleepers to these three interviews, (F(1, 58)=7.35, p<.05). However, after controlling for anxiety and worry, this effect was reduced to non-significance for the ‘sleep’ and ‘worry’ topics, suggesting that anxiety may mediate some of the association between catastrophizing and sleep. However there was still a tendency for poor sleepers to iterate more steps to the ‘hypothetical’ topic, after controlling for anxiety and worry, which also suggests that poor sleepers possess a cognitive style which may predispose them to continue iterating consecutive steps to open-ended tasks regardless of anxiety and worry. Future research should examine whether the presence of this cognitive style is significant in leading to or maintaining insomnia.